(untitled) (The Journal of Plant Protection Sciences, 2022)
Soybean (Glycine max) is the second largest crop in the United States. The annual loss of soybean due to various diseases is approxi mately 2 billion dollars in the U.S. (1). Soy bean cyst nematode (SCN), Heterodera gly cines, is the major pathogen of soybean and was responsible for approximately 500 mil lion in losses in 2010. Some soybean acces sions have resistance to certain isolates of cyst nematode, but none are resistant to all iso lates. To gain new insights into the mecha nism of soybean interaction with the SCN and to further develop the resistant varieties, knowledge of genomics and proteomic of the nematode is important. To devise strategies to control SCN and develop soybeans with broad resistance against SCN, basic information about the nematode’s proteome would provide a better understanding of SCN parasitism and its virulence.